Assessing avian diversity and community composition along a successional gradient in traditional Lacandon Maya agroforests. (19th August 2020) - Falkowski, Tomasz B.; Vázquez‐Pérez, José Raúl; Chankin, Adolfo; Campos‐Beltrán, Atzin Yetlanezi; Rangel‐Salazar, José L.; Cohen, Jonathan B.; Diemont, Stewart A.W.
Abstract: Evidence regarding the ability of agroforests to conserve biological diversity has been mixed; they tend to maintain avian communities with species richness similar to that of undisturbed forest ecosystems but generally do not completely preserve community composition. Using a combination of occupancy modeling and non‐metric multidimensional scaling on point‐count data, we assessed changes in avian community diversity and composition along a successional gradient in traditional Lacandon Maya agroforests and compared them to protected areas in the region. Bird species richness and diversity in Lacandon agroforests peaked in early secondary forest stages. These agroforests' mean Shannon–Weiner diversity was 5% higher than that of nearby protected areas, but their species richness was similar. Community composition in Lacandon agroforests changed throughout succession, with earlier stages supporting communities distinctly characterized by generalist species, while subsequent, less‐intensively managed stages tended to support more forest‐dwellers. The bird community observed in even the most mature secondary forest stages in Lacandon agroforests differed from that of undisturbed rain forest ecosystems. These results demonstrate the potential of traditional Lacandon agroforestry management to conserve avian biodiversity while ensuring food sovereignty for farmers. However, because the community composition of early‐successional stages was different than later stages, shortening fallow cycles and reducing forest cover to increase agricultural production will limit the species this system can support. This study illustrates the value of incorporating traditional agroecosystems into conservation planning as well as maintaining protected areas, because the latter serve as refugia for species that require undisturbed forest habitat in an agroecological matrix. Abstract in Spanish is available with online material. Abstract : The diversity and species richness of bird communities in Lacandon Maya agroforests were similar to those of nearby strictly protected areas. The bird community composition in these traditional agroforests became less dissimilar to that of strict protected areas over the course of succession, but ultimately remained distinct. Given the full suite of ecosystem services they provide, Lacandon agroforests can complement strictly protected areas to support avian conservation and food sovereignty in the Montes Azules Biosphere Reserve region of Chiapas, Mexico. Resumen: La evidencia de la capacidad de los sistemas agroforestales para conservar la diversidad biológica ha sido mixta; aunque estos tienden a mantener comunidades de aves cuya riqueza de especies es similar a la de los ecosistemas forestales no perturbados, en general no completamente conservan la misma composición de especies. Usando una combinación de modelos de ocupación de tiempo‐detección y escalamiento no‐métrico multidimensional en los datos de conteo por puntos, evaluamos los cambios en la diversidad de la comunidad de aves en un gradiente de sucesión en las actividades agroforestales de los Lacandones y los comparó con áreas protegidas en la región. La diversidad y riqueza de especies de aves en los sistemas agroforestales lacandones alcanzó su punto máximo en las primeras etapas de la selva secundaria. Aunque la riqueza de estos sistemas era similar a la de las áreas protegidas cercanas, su diversidad de Shannon–Weiner era 5% mayor. La composición comunitaria en los agroforestales lacandones cambió a lo largo de la sucesión; la comunidad en las primeras etapas soporta especies más generalistas, mientras que las etapas de manejo menos intensivo tendieron a soportar a más habitantes de la selva. Sin embargo, la comunidad de aves observó incluso en los estadios de selva secundaria en los agroforestales lacandones, que diferían de los ecosistemas forestales de referencias y no alteradas. Estos resultados demuestran el potencial de la gestión agroforestal tradicional de los Lacandones para conservar la biodiversidad de aves y garantizar la soberanía alimentaria de los agricultores. Sin embargo, debido a que la composición de la comunidad difería entre etapas sucesivas, acortar los ciclos de barbecho y reducir la cubierta forestal para aumentar la producción agrícola limitará el conjunto de especies que este sistema admite. Este estudio ilustra el valor de incorporar agroecosistemas tradicionales en la planificación de la conservación, además de mantener las áreas protegidas, ya que estas últimas sirven como refugios para especies que requieren hábitats de selva sin perturbaciones en una matriz agroecológica.